Prediksi Harga Emas di Indonesia menggunakan Metode Linear Regression Berbasis Data Historis Antam - Cahya, Titus Dwi; Sumanto, Sumanto; Chaidir, Indra (Universitas Pahlawan Tuanku Tambusai, 2025)
This study uses a simple linear regression method to predict gold prices in Indonesia using historical Antam gold data. Linear regression is applied to model the linear relationship between the 2024 daily gold price (variable Y) and the date (variable X). Model performance is evaluated using Mean Squared Error (MSE) and R-squared (R²) to ensure more stable and accurate results. The evaluation results show that the linear regression model used has an MSE of 1403425123.8609 and an R² of 0.93, indicating good performance in predicting gold prices. This study concludes that the simple linear regression method can be used to predict gold prices throughout the year (long-term), but cannot accurately predict daily prices.